A n i n v e s t i g a t i o n i n t o t h e c h e m i c a l c o m p o s i t i o n o f v a r i o u s s e e d o i l s f o r a p p l i c a t i o n i n c o s m e t i c p r o d u c t s - Khoosal, Sabrina Tanita (My University, 2022)
Due to increased consumer awareness, there has been a strong shift in cosmetic product trends towards more natural and/ or greener alternatives in recent years. This is due to several factors such as cases of adverse effects caused by certain synthetic ingredients in products as well as the awareness of synergistic benefits of natural ingredients. Seed oils are one of the solutions being used to satisfy this newly found demand due to their chemical compositions that have cosmetic, nutritional and medicinal benefits (Antignac et al., 2011; Vermaak et al., 2011; Dangarembizi et al., 2015). Seed oils consist of essential and nonessential fatty acids, antioxidants, and vitamins, amongst other phytochemicals. This makes seed oils useful as emollients, active ingredients or as carriers for other active ingredients (Vermaak et al., 2011; Dangarembizi et al., 2015). The seed oils focused on in this study are from underutilised plants native to, or highly cultivated in Africa (Vermaak et al., 2011; Dangarembizi et al., 2015). They are namely Moringa oleifera (MO), Sclerocarya birrea (Marula), Citrullus lanatus (Kalahari melon), Schinziophyton rautanenii (Mongongo), Adansonia digitate L. (Baobab), and Cannabis sativa L. (Hemp). Other commercially available plant oils included for comparative purposes in the study include avocado oil, olive oil, jojoba seed oil, grapeseed oil and sunflower seed oil. Increasing the commercialisation of these underutilised oils will benefit rural communities involved in harvesting, encourage maintenance of the natural environment, provide more export products and alternative natural ingredients for the cosmetic industry, which will overall benefit our bioeconomy (Zimba et al., 2005; Juliani et al., 2007; Vermaak et al., 2011). Research is therefore needed to contribute to the database of information on these oils to further understand their potential in the natural-based cosmetic sector. To evaluate the economic importance and potential of these seed oils for cosmetic applications, in-depth profiling of the oils were conducted (Cheikhyoussef, 2018). The oil profiles include physico-chemical properties; namely acid value (AV), saponification value (SV), average molecular weight (AMW), ester value (EV), peroxide value (PV), iodine value (IV), specific gravity and the refractive index. Further characterisation of the oils involved Fourier Transform-Infrared Spectroscopy (FT-IR) analysis, antioxidizing abilities using Ultraviolet-visible spectroscopy (UV- iii C1 - Internal use Vis), chemical composition using Nuclear Magnetic Resonance (NMR) Spectroscopy, thermal behaviour using Differential scanning Calorimetry (DSC) as well the fatty acid methyl ester (FAME) profile using Gas Chromatography-Mass Spectrometry (GC-MS) as well as studying the effect of sunlight exposure on the various oils. AV is a reflection of the total acidity of the oil sample; therefore a lower value indicates less degradation and therefore higher quality of the oil and vice versa, the lowest AV amongst the oils of interest was obtained by Baobab oil (0.40 ± 0.01 mg KOH/g oil). Peroxide value (PV) is a chemical characteristic used to determine the extent of oxidative deterioration of the oil at the time of analysis, the lowest PV from the oils of interest belonged to Baobab oil. AV and PV both confirm the stability and high quality of Baobab making it very important to the cosmetic industry as products often have shelf-lives of 12 months. SV is a measure of the chain length of fatty acids present in the oil and is used to calculate an average molecular weight (AMW). The specific SV range optimal for soap making is 188 to 199 mg KOH/ 1g oil (Francis and Tahir, 2016). Therefore from the oils studied, Plush Organics Moringa and Hemp seed oil having SV of 189.23 ± 0.95 mg KOH /1g oil and 195,05 ± 0.56 mg KOH /1g oil respectively, would be most suitable for application in soap making. IV is related to the degree of unsaturation such that the higher the IV the more unsaturated the oil. The IV obtained for the extracted MO oils (65.93-74.99 g/100g) was lower than that obtained for Baobab seed oil (91.30 g/100g) and Kalahari melon seed oil (131.90 g/100g). Relative IV from 1H NMR data for Lefakong farming cold pressed MO oil and Soxhlet extracted MO oil (68.54-69.49 g/100g) was lower than that obtained for Baobab seed oil (76.44 g/100g) and Kalahari melon seed oil (126.36 g/100g). From relative fatty acid percentages, the TUFA% results for the extracted MO oils (33.93-64.33%) is lower than the TUFA% obtained for Baobab seed oil (65.61%) and Kalahari melon seed oil (72.24%). Multiple parameters therefore confirm the result that Kalahari melon seed oil was the most unsaturated followed by Baobab seed oil and MO oil was the least unsaturated from this sample group
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, School of Chemistry, University of the Witwatersrand, Johannesburg, 2022